Forming Condition of Foamy Oil Flow in Depletion Development of Heavy Oil Reservoir - Zhuangzhuang Wang, Yuanxiang Sun, Minglu Ma (Forest Chemicals Review)
The formation of foamy oil can improve the primary recovery of heavy oil reservoir, but it is not very clear under what conditions foamy oil will form. In this paper, depletion experiments were conducted in one-dimensional sandpacks to investigate the effect of oil viscosity, solution gas-oil ratio, pressure depletion rate and formation permeability on foamy oil, and the forming condition of foamy oil flow was determined. The results show that when foamy oil flow exists, oil recovery curve takes an “S pattern” with a sharp rise in the middle section. Lower oil viscosity makes it difficult to form steady foamy oil flow. As solution gas-oil ratio increases, oil recovery first increases and then decreases slightly. There exists an optimum scope of solution gas-oil ratio for foamy oil flow. Foamy oil can only form when pressure depletion rate is high enough. Foamy oil is difficult to flow and gas channeling may easily occur in lower permeable cores. According to the experimental results, forming conditions of foamy oil are concluded preliminarily: live oil viscosity should not be lower than 210 mPa·s, the optimal range of solution gas-oil ratio is 5-26 Sm3/m3, the lowest pressure depletion rate recommended is 5 KPa/min, and formation permeability should be greater than 3000 mD preferably.